2013
DOI: 10.1016/j.jphotobiol.2013.03.007
|View full text |Cite
|
Sign up to set email alerts
|

UVA causes dual inactivation of cathepsin B and L underlying lysosomal dysfunction in human dermal fibroblasts

Abstract: Cutaneous exposure to chronic solar UVA-radiation is a causative factor in photocarcinogenesis and photoaging. Recently, we have identified the thiol-dependent cysteine-protease cathepsin B as a novel UVA-target undergoing photo-oxidative inactivation upstream of autophagic-lysosomal dysfunction in fibroblasts. In this study, we examined UVA effects on a wider range of cathepsins and explored the occurrence of UVA-induced cathepsin inactivation in other cultured skin cell types. In dermal fibroblasts, chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 64 publications
1
28
1
3
Order By: Relevance
“…8,38 Cells (1 × 10 6 ) were lysed in 0.5 ml of chilled lysis buffer. After 10 min incubation on ice, lysates were centrifuged at 10,000 g at 4 °C for 5 min and the supernatant fraction was retained for analysis.…”
Section: Cellular Atp Determinationmentioning
confidence: 99%
See 2 more Smart Citations
“…8,38 Cells (1 × 10 6 ) were lysed in 0.5 ml of chilled lysis buffer. After 10 min incubation on ice, lysates were centrifuged at 10,000 g at 4 °C for 5 min and the supernatant fraction was retained for analysis.…”
Section: Cellular Atp Determinationmentioning
confidence: 99%
“…8 Processing of samples and the protocol were identical to the CTSB activity assay as described above with the following modifications: CTSL determination: After lysis, 50 μL lysate were incubated with 50 μL of reaction buffer containing Ca074 (Sigma, C5732; 1 µM, 15 min) to irreversibly inhibit CTSB, thereby eliminating interference from CTSB-dependent cleavage of the substrate. 91,92 CTSL substrate (Ac-Phe-Arg-AFC, Abcam, ab157769; 200 μM final concentration) was then added and the mixture was incubated for 1 h at 37 °C followed by AFC detection (λex 400 nm, λem 505 nm).…”
Section: Cellular Atp Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…[12] Recent research shows that CatL activity in fibroblasts is significantly suppressed 1 h after four consecutive daily exposures to 9.9 J/cm 2 UVA, whereas its gene expression level remains unchanged. [13] However, repetitive UVA irradiation elevates CatL protein synthesis through increased transcript levels in fibroblasts. [12] Little is known about the molecular mechanisms, whereby UVA induces CatL expression and activity.…”
Section: Introductionmentioning
confidence: 99%
“…However, the results of recent studies have shown that the UVA can also be a potent inductor of DNA damage and may be associated with skin cancer 9 . Protracted exposure to UVA leads to lysosomal dysfunction in human fibroblasts 10 , malignant transformation in human cultured keratinocytes 11 and the formation of skin carcinomas in hairless mice in vivo 12 . Unlike the shorter-wavelength UVB photons, which are almost completely absorbed by the epidermis, the longerwave length UVA photons can reach deeper dermal layer of skin and its blood vessels.…”
Section: Introductionmentioning
confidence: 99%